2013
DOI: 10.1063/1.4815868
|View full text |Cite
|
Sign up to set email alerts
|

Rotating-frame nuclear magnetic resonance study of the distinct dynamics of hydrogen donors in ZnO

Abstract: The rotating-frame spin-lattice relaxation of two types of the hydrogen donors was well distinguished in the 1H nuclear magnetic resonance measurements in a sol-gel prepared ZnO system, providing a unique opportunity to study the distinct proton dynamics. Our study indicates interconversion of the interstitial H (Hi). The population of the mobile Hi showed decrease above ∼370 K, apparently being trapping into the oxygen vacancies resulting in the more stable oxygen-substitutional H (HO). The activation barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
(37 reference statements)
1
0
0
Order By: Relevance
“…Note that recent NMR investigations have shown that at temperatures above 370 K, interstitial hydrogen becomes trapped at the oxygen vacancy with the energy gain of 0.51 eV [58], which gives us further support for the assignment of the 273 cm −1 line to the H O donor. Figure 8 presents Raman spectra of an isochronal annealing series of a ZnO sample that was treated in a mixture of D 2 and H 2 .…”
Section: B Identification Of the Shallow Donor Transition Of H Osupporting
confidence: 71%
“…Note that recent NMR investigations have shown that at temperatures above 370 K, interstitial hydrogen becomes trapped at the oxygen vacancy with the energy gain of 0.51 eV [58], which gives us further support for the assignment of the 273 cm −1 line to the H O donor. Figure 8 presents Raman spectra of an isochronal annealing series of a ZnO sample that was treated in a mixture of D 2 and H 2 .…”
Section: B Identification Of the Shallow Donor Transition Of H Osupporting
confidence: 71%